The role of metastasectomy in renal cell carcinoma. Issue 12 (December 2013) - Josephides, Eleni; Rodriguez-Vida, Alejo; Galazi, Myria; Chowdhury, Simon; Suder, Aneta
Despite significant advances in the systemic treatment of metastatic renal cell carcinoma, long-term survival remains low. A potential way to improve outcomes in selected cases is the use of metastasectomy, which is part of the multimodal treatment of this disease. Although the evidence supporting this approach is limited, we believe it is a reasonable option for certain patients. This review summarizes the evidence supporting this approach.